ANALISIS PENGATURAN PENGELOLAAN KEGIATAN USAHA HULU MIGAS PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-X/2012 - Ahmad, Imran (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Constitutional Court Decision No. 36 / PUU-X / 20012 regarding Testing Act No. 22 of 2001 on Oil and Gas lead the Executive Agency for Upstream Oil and Gas (BP Migas) dissolved. BP Migas declared contrary to the Constitution, specifically Article 33 UUD 1945 because its presence causes the state to lose the right to control oil and gas resources. To provide certainty in the operation of upstream oil and gas after the dissolution of BP Migas, the President issued Presidential Decree No. 9 of 2013, which it formed a surrogate agency BP Migas, the Special Unit of Upstream Oil and Gas (SKK Migas). The subject matter which analyzed these include the existence of SKKMigas that replaces the duties and functions of BP Migas when the review of the Constitutional Court Decision No. 36 / PUU-X / 2012, and how should form upstream oil and gas management arrangement that takes into account the role of state enterprises. The results of this study can be concluded that the existence of SKK Migas is basically the same as BP Migas which has been dissolved. This happens because SKK Migas given the same functions with the task of which is owned by BP Migas. The establishment of SKK Migas to take over the management of upstream oil and gas indicate there are no fundamental changes in the system of management of oil and gas resources after the Constitutional Court Decision No. 36 / PUU-X / 2012, the changes in question are related to the state control over the natural resources of oil and gas. To build energy independence, there must be a concern of the government at the State Company (National Oil Company, NOC).